Development of NDCDB in E-cadastral environment : case study NDCDB in area of Universiti Teknologi Mara MARA Perlis / Norsyahdira Ahmad - Ahmad, Norsyahdira (2019)
e-Cadastral was implementation under 9th Malaysia plan (2006) which can increase productivity in surveying technologies. With that, the aim of this study to provides the National Digital Cadastral Database (NDCDB) in the area of Universiti Teknologi MARA (UITM), Perlis using the e-Cadastral system. The modem of e-Cadastral survey technologies software can produce collection and directly automatically processing survey data during fieldwork. One of the technologies of the e-Cadastral survey is pre-computation (pre-comp) software. The pre-comp software to produce the pre-computation plan using the coordinate GDM2000 and also automatic generate SKL ASCII file. The second of technologies highly advance software in the e- Cadastral survey is e-Title Survey Module (e-TSM) software. e-TSM software can view data capture of survey data, and the survey data will electronic record and calculated which can adopt in the field to finish (F2F) concept under the e-Cadastral environment. Indirectly, the advances in this e-TSM software also can automatically generate 16 ASCII file at the same time. So that, the advantages of this method technology to surveyor are can save time, save cost and also reduce the workforce in survey work. Other than that, the capabilities of survey instrument also crucial in the implementation of e-Cadastral such as Total Station ES instrument. This device used in the e-Cadastral survey to replaces the obsolete land survey instruments. Usually, the e-Cadastral survey cannot be separated with the accuracy and precision. That why JUPEM upgrade their method from standard measurement cadastral works process Bowditch to digital method measurement e-Cadastral work using Least Square Adjustment. The result data survey must be under tolerance and lowest bound according to "Pekeliling KPUP Bil.6 Tahun 2009" (PKPUP 2009) to take the measurement quality of e-Cadastral survey work. In conclusion, the implementation e-Cadastral in survey depends on the capabilities of instruments and software will get the real time results data survey and the work will complete on time and efficient.